GENDER ISSUES IN POPULER CHILDREN’S FAIRY TALES - Andriadi Andriadi (Jurnal Hawa : Studi Pengarus Utamaan Gender dan Anak, 2020)
This study focuses on children's popular fairy tales which are indicated to carry gender issues in the elements of story building. This study aims to: (1) identify gender issues that are subtly aired through popular children's fairy tales; and (2) know the role of parents in dealing with gender issues. This study applied a qualitative method using three popular children's tales as a source of data, namely Putri Salju dan Tujuh Kurcaci, Bawang Merah Bawang Putih, and Keong Mas. The results of the study indicate that several gender issues are subtly exhaled concerning gender bias which is not yet suitable for consumption by childhood. Therefore, the function of parents as guides and filters of children's reading sources is very important so that they can make fairy tales as a means of character education and ignore the elements of the story that are not by their character education and character formation.